Distance Learning (DL) Strategies to Fight Coronavirus (COVID-19) Pandemic at Higher Education in Indonesia - Budi, Hendrik Setia; Ludjen, Jael Segah Mahamiano; Aula, Achmad Chasina; Prathama, Fata Ariestia; Maulana, Ragil; Siswoyo, Lukas Aldhi Hannawan; Prihantono, Agung Sasangko (International Journal of Psychosocial Rehabilitation, 2020)
The coronavirus disease, also known as COVID-19, is a new infectious virus (nCov) spread over 210 countries across the world. This virus is exacerbated in people with underlying systemic health conditions such as diabetes mellitus, hypertension, and cardiovascular disease. The COVID-19 pandemic has adversely impacted on all areas of life, including education, therefore, distance learning (DL) or e-learning is a supportive educational system under this condition. The purpose of this study is to describe the readiness of lecturers and students in the field of dentistry in using the distance learning (DL) system during this pandemic. The simple random sampling method, was used to obtain data from a total of 142 respondents using questionnaires. In the 2nd, 4th, 6th, 8th, and 10th semesters there were approximately 28, 21, 23, 69, and 1 respondent, respectively. From the 142 respondents, 90% stated that they already had personal computers or laptops, while 10% used those belonging to relatives, neighbors, or friends. In accordance with the availability of internet facilities at home, 84% stated that they already had access to the internet, while 16% had none. Related to the quota and stability of internet access, 51% of respondents stated that they were ready with fast internet and sufficient quota, while 49% reported that they were not ready due to limited quota, and unstable internet access. Furthermore, a total of 20 lecturers were given access to a licensed Zoom® account. Lecturers and students stated their readiness to conduct distance learning in a bid to fight COVID-19and support the work from home programs.